Comparing the reprogramming efficiency of mouse embryonic fibroblasts, mouse bone marrow mesenchymal stem cells and bone marrow mononuclear cells to iPSCs - Wang, Lei; Zhu, Mingyan; Guo, Qingsong; Fan, Xiangjun; Lu, Yuhua; Zhu, Shajun; Wang, Yao; Huang, Yan; Wang, Zhiwei (In vitro cellular & developmental biology. Animal, 2012)
Induced pluripotent stem cells have been derived from various cell types via the ectopic expression of a cocktail of transcription factors. Previous studies have reported that induced pluripotent stem cells can be differentiated into multiple somatic cells, providing an invaluable resource in regenerative medicine. In this study, we compared the reprogramming efficiency of mouse embryonic fibroblasts, mouse bone marrow mesenchymal stem cells, and mouse bone marrow mononuclear cells by counting the number of alkaline phosphatase staining positive clones on day 15 after induced pluripotent stem cells induction. We found that a very low number of alkaline phosphatase-staining positive clones were derived from mouse bone marrow mesenchymal stem cells. We then evaluated the pluripotency of the clones by detecting the expression of embryonic stem cells markers and assessing their ability to form embryoid bodies and teratomas. Mouse bone marrow mesenchymal stem cells population is more homogeneous than mouse bone marrow mononuclear cells, which includes a variety of cell types. Our study indicated that the extremely low efficiency of mouse bone marrow mesenchymal stem cells induction implies that mouse bone marrow mesenchymal stem cells may not be a suitable cell type for the induction of induced pluripotent stem cells unless the efficiency of induction can be improved.